The impact of technological competencies on innovation and corporate venturing. (1st January 2012) - Fernández-Pérez, Virginia; Martín-Rojas, Rodrigo
Our study seeks to analyse theoretically and empirically how the technological distinctive competencies (TDCs) positively influence on the organisational performance from an entrepreneurial perspective. To date, very little research has analysed the direct and indirect relationships between these variables. Our study seeks to fill this research gap by analysing theoretically and empirically how different intermediate strategic variables related to entrepreneurship (innovation and corporate venturing) influence the relation between TDCs and organisational performance. The methodology used was LISREL analysis. We then test the model using data from 201 Spanish organisations. It adds theoretical and empirical arguments to the importance of technological distinctive competencies for the organisation. Today's knowledge society requires new CEOs who can confront a reality based on technological knowledge, and foster innovation and corporate venturing to achieve improvements in organisational performance. However, organisations sometimes fail to achieve sustainable competitive advantage due to their limited understanding of the relationships between these strategic variables.